Contribution of Prepregnancy Obesity to Racial and Ethnic Disparities in Severe Maternal Morbidity. Issue 5 (May 2021) - Siddiqui, Ayesha; Azria, Elie; Egorova, Natalia; Deneux-Tharaux, Catherine; Howell, Elizabeth A.
Abstract : OBJECTIVE: To evaluate the role of prepregnancy obesity as a mediator in the association between race–ethnicity and severe maternal morbidity. METHODS: We conducted an analysis on a population-based retrospective cohort study using 2010–2014 birth records linked with hospital discharge data in New York City. A multivariable logistic regression mediation model on a subgroup of the sample consisting of normal-weight and obese women (n=409, 021) calculated the mediation effect of obesity in the association between maternal race–ethnicity and severe maternal morbidity, and the residual effect not mediated by obesity. A sensitivity analysis was conducted excluding the severe maternal morbidity cases due to blood transfusion. RESULTS: Among 591, 455 live births, we identified 15, 158 cases of severe maternal morbidity (256.3/10, 000 deliveries). The severe maternal morbidity rate among obese women was higher than that of normal-weight women (342 vs 216/10, 000 deliveries). Black women had a severe maternal morbidity rate nearly three times higher than White women (420 vs 146/10, 000 deliveries) and the severe maternal morbidity rate among Latinas was nearly twice that of White women (285/10, 000 deliveries). Among women with normal or obese body mass index (BMI) only (n=409, 021), Black race was strongly associated with severe maternal morbidity (adjusted odds ratio [aOR] 3.02, 95% CI 2.88–3.17) but the obesity-mediated effect represented only 3.2% of the total association (aOR 1.03, 95% CI 1.02–1.05). Latina ethnicity was also associated with severe maternal morbidity (aOR 2.01, 95% CI 1.90–2.12) and the obesity-mediated effect was similarly small: 3.4% of the total association (aOR 1.02, 95% CI 1.01–1.03). In a sensitivity analysis excluding blood transfusion, severe maternal morbidity cases found a higher mediation effect of obesity in the association with Black race and Latina ethnicity (15.3% and 15.2% of the total association, respectively). CONCLUSION: Our findings indicate that prepregnancy obesity, a modifiable factor, is a limited driver of racial–ethnic disparities in overall severe maternal morbidity. Abstract : Although both Black race and Latina ethnicity were strongly associated with severe maternal morbidity, obesity mediated only 3% of the observed associations, suggesting other factors deserve more attention.